Revolutionizing quality performance through digitization, technology management, and environmental management: a cutting-edge PLS-SEM model analysis with organizational agility as mediator and culture as moderator - Fangqi, Dong; Irfan, Muhammad; Baloch, Zarbakht (Frontiers in Environmental Science, 2023)
In today's era of increasing environmental awareness, organizations need to consider the environmental economics and management perspective in addition to quality performance.Recent societal changes have led to a significant digital revolution that has made it challenging for industrialized nations to manage technology transfer. Organizations must integrate digitalization, technology, culture, and environmental sustainability to survive in this highly competitive climate. This study examines the relationship between digitalization and technology management and their impact on Total Quality Management (TQM) performance in Pakistani businesses, considering the environmental economics and management perspective. A quantitative approach was taken, and senior executives from the public and private sectors were surveyed to obtain information. The data was analyzed using SMART PLS 3, which utilized Partial Least Squares Structural Equation Modeling(PLS-SEM). The study found that digitalization and technology management significantly enhanced TQM performance, with organization agility mediating and organization culture moderating. The organization's agility also played a crucial role in mediating the relationship between technology management and TQM performance. The findings of this study offer valuable insights for quality management practitioners and policymakers, highlighting the importance of incorporating environmental economics and management practices into an overall quality performance.